PENGARUH PENGETAHUAN AKUNTANSI DAN PENGALAMAN USAHA TERHADAP PENGEMBANGAN USAHA DAN PENGGUNAAN INFORMASI AKUNTANSI SEBAGAI VARIABEL INTERVENING (Kajian Empiris Pada Pelaku Usaha Kecil dan Menengah di Kelurahan Tanjung Rejo Kecamatan Medan Sunggal) - Formaida Tambunan (Universitas Islam Negeri Sumatera Utara, 2019)
This research aims to examine and analyze the influence of accounting knowledge and experience effort towards the development of a mediation effort with the use of accounting information on the perpetrators of the UKM. Research conducted in the village of Tanjung Rejo Medan Sunggal in 2019.This research is quantitative research associate. Population and sample of this research is 40 principals with UKM error rate of 5%. Types and sources of data that dikumulkan is quantitative data and secondary data by analyzing the use test, test the normality assumption linieritas and using path analysis. The conclusions of the results of this study are: 1) influential accounting knowledge against the use of accounting information, whereas business experience has no effect against the use of accounting information accounting knowledge, 2) knowledge of accounting and business experience a positive effect towards enterprise development, and 3) accounting knowledge and business experience have indirect influence through the use of accounting information to the development effort.